2017
DOI: 10.1007/s11589-017-0181-8
|View full text |Cite
|
Sign up to set email alerts
|

Electrical triggering of earthquakes: results of laboratory experiments at spring-block models

Abstract: Recently published results of field and laboratory experiments on the seismic/acoustic response to injection of direct current (DC) pulses into the Earth crust or stressed rock samples raised a question on a possibility of electrical earthquake triggering. A physical mechanism of the considered phenomenon is not clear yet in view of the very low current density (10 -7 -10 -8 A/m 2 ) generated by the pulsed power systems at the epicenter depth (5-10 km) of local earthquakes occurred just after the current injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Our present results from the study of the precursory physical conditions before the Taiwan 7.7 M w EQ provide evidence that the pre-EQ sub-ULF (<1 min) magnetic wave activity may indicate a potential cause and not the result of tectonic stresses. This hypothesis is consistent with the fact that MHD generators have been used to activate local earthquakes (Pulinets and Boyarchuk, 2004;Sorokin et al, 2012;Novikov et al, 2017). The impact of electrical pulses of DC current injected through emitting dipole into the earth crust on the spatial and temporal distribution of weak seismicity has been confirmed (Tarasova et al, 2000;Tarasova, 2002, 2004;Chelidze et al, 2006).…”
Section: Discussionsupporting
confidence: 61%
“…Our present results from the study of the precursory physical conditions before the Taiwan 7.7 M w EQ provide evidence that the pre-EQ sub-ULF (<1 min) magnetic wave activity may indicate a potential cause and not the result of tectonic stresses. This hypothesis is consistent with the fact that MHD generators have been used to activate local earthquakes (Pulinets and Boyarchuk, 2004;Sorokin et al, 2012;Novikov et al, 2017). The impact of electrical pulses of DC current injected through emitting dipole into the earth crust on the spatial and temporal distribution of weak seismicity has been confirmed (Tarasova et al, 2000;Tarasova, 2002, 2004;Chelidze et al, 2006).…”
Section: Discussionsupporting
confidence: 61%
“…It was shown that a response of acoustic emission to electric action characterized crack formations in the sample rises as the sample loading and maximally appears at the stress level of 0.95-0.99 of breaking stress of the geomaterial. The laboratory study of electric triggering of macro events (laboratory "earthquakes") were carried out at simplified slider system [Chelidze et al, 2002] and spring-block model [Novikov et al, 2017] simulated the seismogenic fault. The both experimental facilities are based on the idea that "stick-slip" behavior of the fault is a mechanism of earthquake preparation and occurrence [Brace and Byerlee, 1966].…”
Section: Field and Laboratory Results On Electric/electromagnetic Triggering Of Earthquakes As Motivation Of Researchmentioning
confidence: 99%
“…correlation analysis for complete data sets, both global and regional) to clear a presence of electromagnetic triggering phenomena resulted from solar flares. The earthquake faults sensitive to electromagnetic impacts should have specific parameters favorable for earthquake triggering by electromagnetic impact, namely, subcritical stress level [Novikov et al, 2017], increased electric conductivity, certain fault orientation [Han et al, 2004] for occurrence of geomagnetically induced currents of specific density required for the earthquake triggering. In many cases these parameters are unknown.…”
Section: New Evidence Of Earthquake Triggering By Solar Flarementioning
confidence: 99%
See 1 more Smart Citation
“…Magnetically induced slipping was demonstrated also by Novikov et al [56] [57]; by using almost the same technique they have shown that the sharp slip of a movable sample on the supporting block occurs as the triggering the artificial, laboratory "earthquake" hand-made by electromagnetic pulses. Extensive experiments with magneto-hydrodynamic generators for many years have also detected correlation between magnetic and seismic events [53] [58].…”
Section: Earthquake Control By Human-made Meansmentioning
confidence: 86%